Psychological and neuropsychological status of patients with both blast-related ocular injury and mild traumatic brain injury late after the traumatic event - Бакурідзе, Ніна Григорівна; Бакурідзе, Н. Г.; Bakuridze, Nina H.; Bakuridze, N. G.; Луньов, Віталій Євгенійович; Луньов, В. Є.; Lunov, Vitalii Ye.; Lunov, V. Ie.; Ульянов, Вадим Олексійович; Ульянов, В. О.; Ulianov, Vadym O.; Ulianov, V. O.; et al. (Odesa : SI «The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine», 2024)
Purpose: To determine the psychological and neuropsychological status of patients with both blast-related ocular injury and mild traumatic brain injury (TBI) late after the traumatic event. Material and Methods: Thirty patients with blast-related ocular injury, reduced visual function and comorbid mild TBI were included in the study. The following methods of psychological and neuropsychological assessment were used: formalized interview; Suicidality, Post-traumatic Stress Disorder (PTSD), Alcohol Dependence, and Drug Dependence scales of the Mini-International Neuropsychiatric Interview (MINI); Raven’s Progressive Matrix scale; Personal and Social Performance (PSP) scale; PROMIS® Pain-Interference scale; Hospital Anxiety and Depression Scale (HADS); Mazes subtest of the Neuropsychological Assessment Battery (NAB); and Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). Results: The following significant correlations were found: PSP functioning and support from the family (r = 0.533, p = 0.002); total RBANS score and Mazes subtest score (r = 0.466, p = 0.009); total RBANS score and self-reported stress score (negative correlation, r = -0.492, p = 0.006); HADS depression and self-reported stress score (r = 0.646, p = 0.000114); PROMIS pain scale and PTSD scale (r = 0.482, p = 0.007). No association was found between the number of mild TBI events experienced and neuropsychological and psychological measurements. Conclusion: Blast-related mild TBI concomitant with ocular injury has a substantial and long-term impact on casualty’s cognitive and psychological functions. In such patients, the most prominent cognitive deficits occur in the domain of executive function (including cognitive control and planning and problem-solving skills). In the presence of reduced visual function, these deficits have a substantial impact on total cognitive scores, scores of other psychic functions (namely, attention and memory) and significantly affect the patient’s capacity for independent functioning. Мета – визначити особливості психологічного та нейропсихологічного статусу пацієнтів у віддаленому періоді після вибухової травми ока та легкої ЧМТ. Матеріал та методи. Під спостереженням знаходились пацієнти з вибуховою травмою ока зі зниженням зорових функцій і супутньою легкою ЧМТ. Застосовані методики психологічного та нейропсихологічного дослідження: формалізоване інтерв'ю; окремі шкали клінічної оцінки MINI: суїцидальні тенденції, посттравматичний стресовий розлад, алкогольна залежність, залежність від психоактивних речовин; шкала прогресивних матриць Равена; шкала особистісного і соціального функціонування; опитувальник болі PROMIS®; шпитальна шкала тривоги та депресії HADS; субтест «Лабіринти» (NAB); стандартизована батарея нейропсихологічної оцінки RBANS. Результати. У поранених з вибуховою травмою ока та легкою ЧМТ внаслідок дії вибухової хвилі виявлено значущий зв’язок між рівнем функціювання та підтримкою близьких (r=0,533, p=0,002); загальним балом RBANS та субтестом «Лабіринти» (r=0,466, p=0,009), RBANS і самооцінкою рівня стресу (зворотній зв’язок) (r= –0,492, p=0,006); HADS депресії та самооцінкою рівня стресу (r=0,646, p=0,000114); шкалою хронічного болю PROMIS та шкалою визначення посттравматичного стресового розладу (r=0,482, p=0,007). Не визначено зв’язку між кількістю епізодів легкої ЧМТ та показниками нейропсихологічного та психологічного вимірювання. Висновки. Вибухова травма ока в поєднанні з легкою ЧМТ мають суттєвий і тривалий вплив на когнітивні та психологічні функції постраждалих. У таких хворих основними проявами когнітивного дефіциту є порушення виконавчих функцій, включаючи когнітивний контроль, навички планування та вирішення проблем. Зазначені порушення на фоні зниження зорових функцій мають суттєвий вплив на загальні показники когнітивного статусу та інші психічні функції, а саме увагу та пам'ять, і значно погіршують здатність пацієнтів до самостійного функціонування.
Bakuridze N. G. Psychological and neuropsychological status of patients with both blast-related ocular injury and mild traumatic brain injury late after the traumatic event / N. G. Bakuridze, V. Ie. Lunov, V. O. Ulianov et al. // Ukrainian Journal of Ophthalmology. – Odesa : SI «The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine», 2024. – 5(520). – P. 21-26. Режим доступу: https://hdl.handle.net/11300/32376
Keywords: blast-related ocular injury; mild traumatic brain injury; neuropsychology; clinical psychology; post-traumatic stress disorder; вибухова травма ока; легка черепно-мозкова травма; нейропсихологія; вазопроліферативна пухлина; посттравматичний стресовий розлад